Autoimmune markers in young Malaysian patients with type 1 diabetes mellitus - Nazaimoon, W.M.; Azmi, K.N.; Rasat, R.; Ismail, I.S.; Singaraveloo, M.; Mohamad, W.B.; Letchuman, R.; Sheriff, I.H.; Faridah, I.; Khalid, B.A. (2000)
This study determined the prevalence and significance of autoantibodies to GAD65 (GAD Ab), insulin (IAA), tyrosine-like phosphatase (IA2) and islet-cell (ICA) in a group of 213 young Malaysian Type 1 diabetics, diagnosed before the age of 40 years. Venous blood was taken at fasting, and at 6 minutes post-glucagon (1 mg i.v.). IAA was detected in 47.4, GAD Ab in 33.8, IA2 in 8.9 and ICA in 1.4 of the subjects. When based on post-glucagon C-peptide level of 600 pmol/L, 172 (80.7) patients had inadequate pancreatic reserve, while the remainder 41(19.3) showed normal response. The autoantibodies, either alone or in combination, were detectable in both groups of patients; higher prevalence in those with poor or no beta-cell function (73.3 versus 46.3, p = 0.0001). Although the prevalence of GAD Ab was highest in newly diagnosed patients (< 5 years), unlike IA2 and ICA, the marker remained detectable in 24-25 of those patients with long-standing disease. Nineteen patients could probably belong to the "latent autoimmune diabetes in adults (LADA)" subset, where pancreatic reserve was adequate but patients had detectable autoantibodies and insulin-requiring. On the other hand, 68 of the 213 patients (32) were seronegative, but presented with near or total beta-cell destruction. Thus, as has also been suggested by others, there is indeed etiological differences between the Asian and the Caucasian Type 1 diabetics, and, there is also the possibility that other, but unknown autoantigens are involved in causing the pancreatic damage.